Antifungal, antiradical and cytotoxic activities of extractives obtained from Tagetes patula L. (Asteraceae), a potential acaricide plant species. (June 2016) - Politi, Flávio A.S.; Queiroz-Fernandes, Geisiany M.; Rodrigues, Edvânio R.; Freitas, Jolindo A.; Pietro, Rosemeire C.L.R.
Abstract: Tagetes patula L. shows a complex chemical composition, ranging from glycosylated flavonoids and thiophenes in extracts until terpenoids in the essential oil. In the present study, due to this rich flavonoidic constitution, its antioxidant potential was determined, having shown values of antiradical percentage superior to reference compounds, mainly the extracts prepared with flowers. Previous studies performed emphasized the acaricide potential of T. patula and thus, the present study aimed to verify the action of extractives obtained from aerial parts on growth of entomopathogenic fungi related to biological control of brown dog tick Rhipicephalus sanguineus and the action against pathogenic fungi closely associated with pets. None of the samples inhibited the growth of strains of Beauveria bassiana or Metarhizium anisopliae, enabling feasible future studies of synergism on acaricide activity of formulations containing fungi and extracts. The antimicrobial activity of ethanolic extract of flowers (FlEtOH70% ) against Microsporum canis and Trichophyton rubrum was significant (193.3 μg/mL and 253.9 μg/mL, respectively), as well as ethanolic extract from aerial parts (APEtOH70% ) against T. rubrum (312.5 μg/mL). In order to ensure the safety of a topical formulation containing the extractives of T. patula, the cytotoxic potential of these samples were tested in murine macrophages cells. At higher concentrations all extracts were quite lethal, with IC50 ranging from 210.96 μg/mL to 468.75 μg/mL for APEtOH70% and FlEtOH70%, respectively. These results suggest that the application of a product containing T. patula extractives in the control of ticks could be used, at principle, only on the environment. Highlights: T. patula showed values of antiradical percentage superior to proven reference antioxidant compounds. No significant results against dermatophytes, none of the extracts inhibited B. bassiana or M. anisopliae . High cytotoxic activity of extracts suggests the application of products developed against ticks only on the environment.